Electromechanical and robot‐assisted arm training for improving activities of daily living, arm function, and arm muscle strength after stroke - Mehrholz, Jan (Cochrane Database Syst Rev, 2015)
BACKGROUND: Electromechanical and robot‐assisted arm training devices are used in rehabilitation, and may help to improve arm function after stroke. OBJECTIVES: To assess the effectiveness of electromechanical and robot‐assisted arm training for improving activities of daily living, arm function, and arm muscle strength in people after stroke. We also assessed the acceptability and safety of the therapy. SEARCH METHODS: We searched the Cochrane Stroke Group's Trials Register (last searched February 2015), the Cochrane Central Register of Controlled Trials (CENTRAL) (the Cochrane Library 2015, Issue 3), MEDLINE (1950 to March 2015), EMBASE (1980 to March 2015), CINAHL (1982 to March 2015), AMED (1985 to March 2015), SPORTDiscus (1949 to March 2015), PEDro (searched April 2015), Compendex (1972 to March 2015), and Inspec (1969 to March 2015). We also handsearched relevant conference proceedings, searched trials and research registers, checked reference lists, and contacted trialists, experts, and researchers in our field, as well as manufacturers of commercial devices. SELECTION CRITERIA: Randomised controlled trials comparing electromechanical and robot‐assisted arm training for recovery of arm function with other rehabilitation or placebo interventions, or no treatment, for people after stroke. DATA COLLECTION AND ANALYSIS: Two review authors independently selected trials for inclusion, assessed trial quality and risk of bias, and extracted data. We contacted trialists for additional information. We analysed the results as standardised mean differences (SMDs) for continuous variables and risk differences (RDs) for dichotomous variables. MAIN RESULTS: We included 34 trials (involving 1160 participants) in this update of our review. Electromechanical and robot‐assisted arm training improved activities of daily living scores (SMD 0.37, 95% confidence interval (CI) 0.11 to 0.64, P = 0.005, I² = 62%), arm function (SMD 0.35, 95% CI 0.18 to 0.51, P < 0.0001, I² = 36%), and arm muscle strength (SMD 0.36, 95% CI 0.01 to 0.70, P = 0.04, I² = 72%), but the quality of the evidence was low to very low. Electromechanical and robot‐assisted arm training did not increase the risk of participant drop‐out (RD 0.00, 95% CI ‐0.02 to 0.03, P = 0.84, I² = 0%) with moderate‐quality evidence, and adverse events were rare. AUTHORS' CONCLUSIONS: People who receive electromechanical and robot‐assisted arm and hand training after stroke might improve their activities of daily living, arm and hand function, and arm and hand muscle strength. However, the results must be interpreted with caution because the quality of the evidence was low to very low, and there were variations between the trials in the intensity, duration, and amount of training; type of treatment; and participant characteristics.